2010
DOI: 10.1186/1471-244x-10-58
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal intention, psychosocial factors and referral to further treatment: A one-year cross-sectional study of self-poisoning

Abstract: BackgroundPatients treated for self-poisoning have an increased risk of death, both by natural and unnatural causes. The follow-up of these patients is therefore of great importance. The aim of this study was to explore the differences in psychosocial factors and referrals to follow-up among self-poisoning patients according to their evaluated intention.MethodsA cross-sectional multicenter study of all 908 admissions to hospital because of self-poisoning in Oslo during one year was completed. Fifty-four percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
3
19
1
6
Order By: Relevance
“…Bjornaas et al (2010a) reported that of all self-poisoning incidents, 37% were suicide attempts, 26% were appeals for help and 38% were related to substance abuse. Studies conducted in our country have shown that most of the poisoning cases are associated with suicide attempts and observed in women (Goksu et al 2002;Cetin et al 2004;Guloglu and Kara 2005;Gunduz et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Bjornaas et al (2010a) reported that of all self-poisoning incidents, 37% were suicide attempts, 26% were appeals for help and 38% were related to substance abuse. Studies conducted in our country have shown that most of the poisoning cases are associated with suicide attempts and observed in women (Goksu et al 2002;Cetin et al 2004;Guloglu and Kara 2005;Gunduz et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…İntihar girişimi ve intihar olayı birbirinden ayrı kavramlar değildir (2 Hastaların iş durumları incelendiğinde, kadın hastaların %73.03'ünün, erkek hastaların %77.18'inin çalışmadığı saptandı. İntihar vakalarının çoğunun çalışmayan erkek ve kadınlar olduğu ve işsizliğin intihar riski ile bağlantılı olduğu bilinmektedir (10)(11)(12). Çalışmada hastaların %64.18'inin kadın, %35.82'sinin erkek olduğu saptandı.…”
Section: öZetunclassified
“…Dette er sammenfallende med funn i andre studier. Bjornaas et al, 2010). Rusmisbruk var en risikofaktor for overdødelighet i 20-årsperioden, men til tross for dette utskrives mange av disse forgiftningene uten tilbud om oppfølging så lenge de ikke blir vurdert som suicidale.…”
unclassified
“…I denne studien så vi en overdøde-lighet av alle årsaker, ikke bare rusrelaterte dødsfall. I en studie fra Oslo i 2003 ble 36 % av rusrelaterte forgiftninger utskrevet uten oppfølging, ikke engang hos fastlegen (Bjornaas et al, 2010). Dette kan ikke forsvares med tanke på deres dårlige prognose på lang sikt, og tilbudet til denne pasientgruppen bør styrkes.…”
unclassified
See 1 more Smart Citation